Аналитическое решение задачи математического маделирования движения центра масс подвижной платформы - Ковтонюк, И. Б.; Шаблий, Г. Ф.; Волосников, С. А. (НТУ "ХПИ", 2015)
Наведено аналітичне рішення задачі математичного моделювання руху центра мас рухомої платформи, яке може бути використане при визначенні траєкторії руху транспортних об’єктів типу "рухома платформа – силова установка".

The analytical solution of mathematical modeling of the center of mass moving platform that can be used in determining the trajectory of transport objects such as "mobile platform – power plant."
Analytical solution of mathematical modeling of the center of mass moving platform
Keywords: система дифференциальных уравнений; силовая установка; преобразование Лапласа; координаты